Article Review: Multiple Sclerosis - Al-ma'mouri, May Y. Al-ma'mouri (Journal for Research in Applied Sciences and Biotechnology, 2024)
Neurology still puzzles about multiple sclerosis (MS). This comprehensive overview explores MS's history, epidemiology, etiology, clinical manifestations, diagnostic tools, and treatment options. From historical awareness to cutting-edge research, we traverse MS's complex world with a focus on the past and future. Genetics, environment, and migration interact to create geographic riddles in MS prevalence. MS's sensory and cognitive symptoms show its significant influence. Advanced imaging technology and diagnostic criteria enable accurate and quick identification. While transformational, disease-modifying treatments require a tailored approach. Advances have left crucial gaps, prompting researchers, physicians, and policymakers to continue. This in-depth investigation of MS combines historical and future perspectives to emphasize the urgency and possibility of solving this complicated neurological puzzle.